INFORMATION SYSTEM ON BATU TEGI DAM BASED ON MOBILE WEB - Suningsih Suningsih (International Journal of Artificial Intelligence and Robotic Technology, 2022)
Tourist attractions in the Tanggamus district have Various tourist attractions that can be visited such as the Tegi stone dam and others. The lack of need to obtain information quickly and easily about Batu Tegi dam tourism, is the reason that underlies the authors to create an information system for Batu Tegi dam tourism. In making a mobile web-based information system, the method used is the System Development Life Cycle (SDLC) method. This method includes needs analysis, system design, implementation, testing phase, and maintenance, followed by making applications using HTML programming as web pages, PHP for web designing. dynamic, CSS to control the appearance on the web, MySQL database as a data base. The results of this information system research for Tegi Batu Dam tourist attractions can help users search for Tegi Batu Dam tourism objects and get information on Tegi Batu Dam tourist attractions, and can be used to promote Tegi Batu Dam tourist attractions in Tanggamus Regency